2022
DOI: 10.1007/s11356-022-22051-7
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins attenuated liver damage and suppressed fibrosis in CCl4-treated rats

Abstract: Liver damage and fibrosis are serious health problems without effective treatment. Proanthocyanidins (PAs) are flavonoids with several biological effects. We investigated the potential anti-fibrotic effect of proanthocyanidins on carbon tetrachloride (CCl4)-induced liver injury and fibrosis. Liver fibrosis was induced by oral administration of CCl4 three times a week for 5 and 9 weeks. PAs were daily administered in a dose of 500 mg/kg bw. Animals were divided into five groups: control groups, olive oil-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Our study found that CCl4 increased the protein expression of the caspase-3 protein, showing that CCl4 can induce liver cell apoptosis. Our result agrees with (Deniz et al, 2019;Wang & Wu, 2019;Amer et al, 2022), who found that CCl4 increased caspase 3 activity, which indicates that apoptosis initiated the development of liver damage. Mitochondria are the main organelle that regulates apoptosis because they are the major site for producing energy and generating ROS.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that CCl4 increased the protein expression of the caspase-3 protein, showing that CCl4 can induce liver cell apoptosis. Our result agrees with (Deniz et al, 2019;Wang & Wu, 2019;Amer et al, 2022), who found that CCl4 increased caspase 3 activity, which indicates that apoptosis initiated the development of liver damage. Mitochondria are the main organelle that regulates apoptosis because they are the major site for producing energy and generating ROS.…”
Section: Discussionsupporting
confidence: 92%
“…The outcomes of this study revealed that liver enzyme amplification is coupled with excessive lipid peroxidation and oxidative stress, as demonstrated by augmented MDA and diminished antioxidant enzymes. Lipid peroxidation-induced damage caused an upsurge in the hepatocytes’ cellular permeability with protein leakage, including aminotransferases, into serum, indicating hepatic injury and necrosis [ 56 ]. GSH is a vital protein thiol, which coordinates the body’s defense system against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response has been reported as a critical process in CCl 4 -induced liver damage [ 56 ]. As previously described, CCl 4 -induced acute liver injury is closely associated with inflammation by elevating pro-inflammatory cytokine secretion [ 38 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The swollen mitochondria that were noticed in CCL4-treated group may be a sign of hepatocytes apoptosis. Amer et al [46] stated that mitochondria are the chief organelle that controls apoptosis because they are the main site for energy creation.…”
Section: Fading Nuclei Of Hepatocytes and Karyolysis Observed In Curr...mentioning
confidence: 99%